Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Differential effects of microplastic exposure on leaf shredding rates of invasive and native amphipod crustaceans - Rose M. Griffith; James W. E. Dickey; Hannah M. Williams; Jack V. Johnson; Gary Hardiman; Jaimie T. A. Dick (Biological Invasions, 2024)
There is growing concern surrounding the pervasive impacts of microplastic pollution, but despite increasing interest in this area there remains limited understanding of its disruption to biological communities and the ecosystem services they provide. One such service is the breakdown of leaf litter in freshwaters by invertebrate shredders, such as Gammarus spp. , that directly and indirectly provides resources for many other species. This study investigates the effect of microplastic exposure on leaf consumption by two Gammarus species in Ireland, the native Gammarus duebeni celticus , and the invasive Gammarus pulex . Individuals were exposed to 40–48 μm polyethylene particles for 24 h at a range of concentrations (20–200,000 MP/L), with the amount of leaf consumption in that time frame recorded. Microplastics did not affect the feeding rate of either species at environmentally relevant concentrations, indicating that ecosystem services currently provided by our study species are sustainable. However, at higher microplastic concentrations the feeding rate of G. d. celticus was significantly reduced, whereas G. pulex remained unaffected, drawing attention to species-specific and native-invader differences in microplastic impacts. The results of our study further contribute to the observed pattern that invasive species, including various amphipod species, often display a higher tolerance to environmental stressors compared to their native counterparts. This research highlights the need for mitigation of ongoing and increasing microplastic pollution that could differentially influence key ecosystem services and functions.

A holistic and comprehensive data approach validates the distribution of the critically endangered flapper skate ( Dipturus intermedius ) - Amy Garbett; Sophie L. Loca; Thomas Barreau; Manuel Biscoito; Caroline Bradley; Joe Breen; Maurice Clarke; Jim R. Ellis; Andrew M. Griffiths; Gary Hannon; Klara Jakobsdóttir; Claudia Junge; et al. (Journal of Fish Biology, 2023)
Morphological similarities between skates of the genus Dipturus in the north‐eastern Atlantic and Mediterranean have resulted in longstanding confusion, misidentification and misreporting. Current evidence indicates that the common skate is best explained as two species, the flapper skate ( Dipturus intermedius ) and the common blue skate ( D. batis ). However, some management and conservation initiatives developed prior to the separation continue to refer to common skate (as ‘ D. batis’ ). This taxonomic uncertainty can lead to errors in estimating population viability, distribution range, and impact on fisheries management and conservation status. Here, we demonstrate how a concerted taxonomic approach, using molecular data and a combination of survey, angler and fisheries data, in addition to expert witness statements, can be used to build a higher resolution picture of the current distribution of D. intermedius . Collated data indicate that flapper skate has a more constrained distribution compared to the perceived distribution of the ‘common skate’, with most observations recorded from Norway and the western and northern seaboards of Ireland and Scotland, with occasional specimens from Portugal and the Azores. Overall, the revised spatial distribution of D. intermedius has significantly reduced the extant range of the species, indicating a possibly fragmented distribution range.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Resilient amphipods: Gammarid predatory behaviour is unaffected by microplastic exposure and deoxygenation - Rose M. Griffith; Ross N. Cuthbert; Jack V. Johnson; Gary Hardiman; Jaimie T.A. Dick (Science of The Total Environment, 2023)

Tidewater glaciers as “climate refugia” for zooplankton-dependent food web in Kongsfjorden, Svalbard - Haakon Hop; Anette Wold; Mikko Vihtakari; Philipp Assmy; Piotr Kuklinski; Slawomir Kwasniewski; Gary P. Griffith; Olga Pavlova; Pedro Duarte; Harald Steen (Frontiers in Marine Science, 2023)
With climate warming, many tidewater glaciers are retreating. Fresh, sediment-rich sub-glacial meltwater is discharged at the glacier grounding line, where it mixes with deep marine water resulting in an upwelling of a plume visible in front of the glacial wall. Zooplankton may suffer increased mortality within the plume due to osmotic shock when brought in contact with the rising meltwater. The constant replenishment of zooplankton and juvenile fish to the surface areas attracts surface-foraging seabirds. Because access to other feeding areas, such as the marginal ice zone, has become energetically costly due to reduced sea-ice extent, glacial plumes may become increasingly important as “climate refugia” providing enhanced prey availability. Here, we investigated zooplankton concentrations within the plume and adjacent waters of four tidewater glaciers in Kongsfjorden, Svalbard, in early August 2016 and late July 2017. Our aim was to compare the zooplankton composition, abundance, and isotopic signatures within the plumes to those in adjacent fjord and shelf waters. Our hypothesis was that the plumes resulted in increased zooplankton mortality through osmotic shock and increased prey availability to predators. The mortality due to osmotic shock in the glacial plume was low (<5% dead organisms in samples), although slightly higher than in surrounding waters. This indicates that plumes are inefficient “death traps” for zooplankton. However, the high abundance and biomass of zooplankton within plume areas suggest that the “elevator effect” of rising glacial water supplies zooplankton to the sea surface, thereby enhancing prey availability for surface-feeding seabirds. Thus, our study provides evidence that glacial plumes are important as “climate refugia” for foraging seabirds. Stable isotope signatures showed that the glacial bay zooplankton and fish community represent a distinct isotopic niche. Additionally, zooplankton mortality associated with the plume estimated over 100-days of melt season supports a flux of 12.8 tonnes of organic carbon to benthic communities in the glacial bays. Benthic scavengers, such as Onisimus caricus and Anonyx nugax , were abundant in the glacial bay, where they feed on sinking organic matter.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Negative impacts of invasive predators used as biological control agents against the pest snail Lissachatina fulica: the snail Euglandina ‘rosea’ and the flatworm Platydemus manokwari - Justin Gerlach; Gary M. Barker; Cindy S. Bick; Philippe Bouchet; Gilianne Brodie; Carl C. Christensen; Timothy Collins; Trevor Coote; Robert H. Cowie; G. Curt Fiedler; Owen L. Griffiths; F. B. Vincent Florens; et al. (Biological Invasions, 2021)
Since 1955 snails of the Euglandina rosea species complex and Platydemus manokwari flatworms were widely introduced in attempted biological control of giant African snails ( Lissachatina fulica ) but have been implicated in the mass extinction of Pacific island snails. We review the histories of the 60 introductions and their impacts on L. fulica and native snails. Since 1993 there have been unofficial releases of Euglandina within island groups. Only three official P. manokwari releases took place, but new populations are being recorded at an increasing rate, probably because of accidental introduction. Claims that these predators controlled L. fulica cannot be substantiated; in some cases pest snail declines coincided with predator arrival but concomitant declines occurred elsewhere in the absence of the predator and the declines in some cases were only temporary. In the Hawaiian Islands, although there had been some earlier declines of native snails, the Euglandina impacts on native snails are clear with rapid decline of many endemic Hawaiian Achatinellinae following predator arrival. In the Society Islands, Partulidae tree snail populations remained stable until Euglandina introduction, when declines were extremely rapid with an exact correspondence between predator arrival and tree snail decline. Platydemus manokwari invasion coincides with native snail declines on some islands, notably the Ogasawara Islands of Japan, and its invasion of Florida has led to mass mortality of Liguus spp. tree snails. We conclude that Euglandina and P. manokwari are not effective biocontrol agents, but do have major negative effects on native snail faunas. These predatory snails and flatworms are generalist predators and as such are not suitable for biological control.

Marine Important Bird and Biodiversity Areas for Penguins in Antarctica, Targets for Conservation Action - Jonathan Handley; Marie-Morgane Rouyer; Elizabeth J. Pearmain; Victoria Warwick-Evans; Katharina Teschke; Jefferson T. Hinke; Heather Lynch; Louise Emmerson; Colin Southwell; Gary Griffith; César A. Cárdenas; Aldina M. A. Franco; et al. (Frontiers in Marine Science, 2021)
Global targets for area-based conservation and management must move beyond threshold-based targets alone and must account for the quality of such areas. In the Southern Ocean around Antarctica, a region where key biodiversity faces unprecedented risks from climate change and where there is a growing demand to extract resources, a number of marine areas have been afforded enhanced conservation or management measures through two adopted marine protected areas (MPAs). However, evidence suggests that additional high quality areas could benefit from a proposed network of MPAs. Penguins offer a particular opportunity to identify high quality areas because these birds, as highly visible central-place foragers, are considered indicator species whose populations reflect the state of the surrounding marine environment. We compiled a comprehensive dataset of the location of penguin colonies and their associated abundance estimates in Antarctica. We then estimated the at-sea distribution of birds based on information derived from tracking data and through the application of a modified foraging radius approach with a density decay function to identify some of the most important marine areas for chick-rearing adult penguins throughout waters surrounding Antarctica following the Important Bird and Biodiversity Area (IBA) framework. Additionally, we assessed how marine IBAs overlapped with the currently adopted and proposed network of key management areas (primarily MPAs), and how the krill fishery likely overlapped with marine IBAs over the past five decades. We identified 63 marine IBAs throughout Antarctic waters and found that were the proposed MPAs to be adopted, the permanent conservation of high quality areas for penguin species would increase by between 49 and 100% depending on the species. Furthermore, our data show that, despite a generally contracting range of operation by the krill fishery in Antarctica over the past five decades, a consistently disproportionate amount of krill is being harvested within marine IBAs compared to the total area in which the fishery operates. Our results support the designation of the proposed MPA network and offer additional guidance as to where decision-makers should act before further perturbation occurs in the Antarctic marine ecosystem.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Identifying important species that amplify or mitigate the interactive effects of human impacts on marine food webs - Gary P. Griffith; Peter G. Strutton; Jayson M. Semmens; Elizabeth A. Fulton (Conservation Biology, 2019)
Some species may have a larger role than others in the transfer of complex effects of multiple human stressors, such as changes in biomass, through marine food webs. We devised a novel approach to identify such species. We constructed annual interaction‐effect networks (IENs) of the simulated changes in biomass between species of the southeastern Australian marine system. Each annual IEN was composed of the species linked by either an additive (sum of the individual stressor response), synergistic (lower biomass compared with additive effects), or antagonistic (greater biomass compared with additive effects) response to the interaction effect of ocean warming, ocean acidification, and fisheries. Structurally, over the simulation period, the number of species and links in the synergistic IENs increased and the network structure became more stable. The stability of the antagonistic IENs decreased and became more vulnerable to the loss of species. In contrast, there was no change in the structural attributes of species linked by an additive response. Using indices common in food‐web and network theory, we identified the species in each IEN for which a change in biomass from stressor effects would disproportionately affect the biomass of other species via direct and indirect local, intermediate, and global predator–prey feeding interactions. Knowing the species that transfer the most synergistic or antagonistic responses in a food‐web may inform conservation under increasing multiple‐stressor impacts.

Isotopic evidence of biotrophy and unusual nitrogen nutrition in soil‐dwelling Hygrophoraceae - Hans Halbwachs; Gary L. Easton; Roland Bol; Erik A. Hobbie; Mark H Garnett; Derek Peršoh; Liz Dixon; Nick Ostle; Peter Karasch; Gareth W. Griffith (Environmental Microbiology, 2018)
Summary Several lines of evidence suggest that the agaricoid, non‐ectomycorrhizal members of the family Hygrophoraceae (waxcaps) are biotrophic with unusual nitrogen nutrition. However, methods for the axenic culture and lab‐based study of these organisms remain to be developed, so our current knowledge is limited to field‐based investigations. Addition of nitrogen, lime or organophosphate pesticide at an experimental field site (Sourhope) suppressed fruiting of waxcap basidiocarps. Furthermore, stable isotope natural abundance in basidiocarps were unusually high in 15 N and low in 13 C, the latter consistent with mycorrhizal nutritional status. Similar patterns were found in waxcap basidiocarps from diverse habitats across four continents. Additional data from 14 C analysis of basidiocarps and 13 C pulse label experiments suggest that these fungi are not saprotrophs but rather biotrophic endophytes and possibly mycorrhizal. The consistently high but variable δ 15 N values (10–20‰) of basidiocarps further indicate that N acquisition or processing differ from other fungi; we suggest that N may be derived from acquisition of N via soil fauna high in the food chain.

Climate change alters stability and species potential interactions in a large marine ecosystem - Gary P. Griffith; Peter G. Strutton; Jayson M. Semmens (Global Change Biology, 2018)
We have little empirical evidence of how large‐scale overlaps between large numbers of marine species may have altered in response to human impacts. Here, we synthesized all available distribution data (>1 million records) since 1992 for 61 species of the East Australian marine ecosystem, a global hot spot of ocean warming and continuing fisheries exploitation. Using a novel approach, we constructed networks of the annual changes in geographical overlaps between species. Using indices of changes in species overlap, we quantified changes in the ecosystem stability, species robustness, species sensitivity and structural keystone species. We then compared the species overlap indices with environmental and fisheries data to identify potential factors leading to the changes in distributional overlaps between species. We found that the structure of the ecosystem has changed with a decrease in asymmetrical geographical overlaps between species. This suggests that the ecosystem has become less stable and potentially more susceptible to environmental perturbations. Most species have shown a decrease in overlaps with other species. The greatest decrease in species overlap robustness and sensitivity to the loss of other species has occurred in the pelagic community. Some demersal species have become more robust and less sensitive. Pelagic structural keystone species, predominately the tunas and billfish, have been replaced by demersal fish species. The changes in species overlap were strongly correlated with regional oceanographic changes, in particular increasing ocean warming and the southward transport of warmer and saltier water with the East Australian Current, but less correlated with fisheries catch. Our study illustrates how large‐scale multispecies distribution changes can help identify structural changes in marine ecosystems associated with climate change.

Population‐level consequences for wild fish exposed to sublethal concentrations of chemicals – a critical review - Patrick B Hamilton; Ian G Cowx; Marjorie F Oleksiak; Andrew M Griffiths; Mats Grahn; Jamie R Stevens; Gary R Carvalho; Elizabeth Nicol; Charles R Tyler (Fish and Fisheries, 2016)
Concentrated chemical spills have been shown to impact adversely on fish populations and even cause localized population extinctions. Evaluating population‐level impacts of sublethal exposure concentrations is, however, complex and confounded by other environmental pressures. Applying effect measures derived from laboratory‐based chemical exposures to impacts in wild fish populations is constrained by uncertainty on how biochemical response measures (biomarkers) translate into health outcomes, lack of available data for chronic exposures and the many uncertainties in available fish population models. Furthermore, wild fish show phenotypic plasticity and local adaptations can occur that adds geographic and temporal variance on responses. Such population‐level factors are rarely considered in the chemical risk assessment process and can probably be derived only from studies on wild fish. Molecular technologies, including microsatellite and SNP genotyping, and RNAS eq for gene expression studies, are advancing our understanding of mechanisms of eco‐toxicological response, tolerance, adaptation and selection in wild populations. We examine critically the application of such approaches with examples including using microsatellites that has identified roach ( Rutilus rutilus ) populations living in rivers contaminated with sewage effluents that are self‐sustaining, and studies of stickleback ( Gasterosteus aculeatus ) and killifish ( Fundulus heteroclitus ) that have identified genomic regions under selection putatively related to pollution tolerance. Integrating data on biological effects between laboratory‐based studies and wild populations, and building understanding on adaptive responses to sublethal exposure are some of the priority research areas for more effective evaluation of population risks and resilience to contaminant exposure.

Predicting Interactions among Fishing, Ocean Warming, and Ocean Acidification in a Marine System with Whole‐Ecosystem Models - Gary P. Griffith; Elizabeth A. Fulton; Rebecca Gorton; Anthony J. Richardson (Conservation Biology, 2012)
An important challenge for conservation is a quantitative understanding of how multiple human stressors will interact to mitigate or exacerbate global environmental change at a community or ecosystem level. We explored the interaction effects of fishing, ocean warming, and ocean acidification over time on 60 functional groups of species in the southeastern Australian marine ecosystem. We tracked changes in relative biomass within a coupled dynamic whole‐ecosystem modeling framework that included the biophysical system, human effects, socioeconomics, and management evaluation. We estimated the individual, additive, and interactive effects on the ecosystem and for five community groups (top predators, fishes, benthic invertebrates, plankton, and primary producers). We calculated the size and direction of interaction effects with an additive null model and interpreted results as synergistic (amplified stress), additive (no additional stress), or antagonistic (reduced stress). Individually, only ocean acidification had a negative effect on total biomass. Fishing and ocean warming and ocean warming with ocean acidification had an additive effect on biomass. Adding fishing to ocean warming and ocean acidification significantly changed the direction and magnitude of the interaction effect to a synergistic response on biomass. The interaction effect depended on the response level examined (ecosystem vs. community). For communities, the size, direction, and type of interaction effect varied depending on the combination of stressors. Top predator and fish biomass had a synergistic response to the interaction of all three stressors, whereas biomass of benthic invertebrates responded antagonistically. With our approach, we were able to identify the regional effects of fishing on the size and direction of the interacting effects of ocean warming and ocean acidification . Predicción de Interacciones entre Pesca, Calentamiento de Océanos y Acidificación de Océanos en un Sistema Marino con Modelos de Ecosistemas Completos

Effects of fishing and acidification‐related benthic mortality on the southeast Australian marine ecosystem - GARY P. GRIFFITH; ELIZABETH A. FULTON; ANTHONY J. RICHARDSON (Global Change Biology, 2011)
Oceanic uptake of anthropogenic carbon dioxide (CO 2 ) is altering the carbonate chemistry of seawater, with potentially negative consequences for many calcifying marine organisms. At the same time, increasing fisheries exploitation is impacting on marine ecosystems. Here, using increased benthic‐invertebrate mortality as a proxy for effects of ocean acidification, the potential impact of the two stressors of fishing and acidification on the southeast Australian marine ecosystem to year 2050 was explored. The individual and interaction effects of the two stressors on biomass and diversity were examined for the entire ecosystem and for regional assemblages. For 61 functional groups or species, the cumulative effects of moderate ocean acidification and fishing were additive (30%), synergistic (33%), and antagonistic (37%). Strong ocean acidification resulted in additive (22%), synergistic (40%), and antagonistic (38%) effects. The greatest impact was on the demersal food web, with fishing impacting predation and acidification affecting benthic production. Areas that have been subject to intensive fishing were the most susceptible to acidification effect, although fishing also mitigated some of the decline in biodiversity observed with moderate acidification. The model suggested that ocean acidification and long‐term fisheries exploitation could act synergistically with the increasing sensitivity to change from long‐term (decades) fisheries exploitation potentially causing unexpected restructuring of the pelagic and demersal food webs. Major regime shifts occur around year 2040. Greater focus is needed on how differential fisheries exploitation of marine resources may exacerbate or accelerate effects of environmental changes such as ocean acidification.

Remote sensing classification of grass seed cropping practices in western Oregon - George W. Mueller-Warrant; Gerald W. Whittaker; Stephen M. Griffith; Gary M. Banowetz; Bruce D. Dugger; Tiffany S. Garcia; Guillermo Giannico; Kathryn L. Boyer; Brenda C. McComb (International Journal of Remote Sensing, 2011)

Reproductive biology of the commercially and recreationally important cobia Rachycentron canadum in northeastern Australia - Tonya D. van der Velde; Shane P. Griffiths; Gary C. Fry (Fisheries Science, 2010)

Diadinoxanthin cycle of the bottom ice algal community during spring in McMurdo Sound, Antarctica - Gary P. Griffith; Ross Vennell; Miles D. Lamare (Polar Biology, 2009)

Synthesis and pharmacological characterization of [125I]MRS1898, a high-affinity, selective radioligand for the rat A3 adenosine receptor - Zhan-Guo Gao; Bao Teng; Haitao Wu; Bhalchandra V. Joshi; Gary L. Griffiths; Kenneth A. Jacobson (Purinergic Signalling, 2009)

Geography of asbestos contamination near the World Trade Center site - William C. Thayer; Daniel A. Griffith; Gary L. Diamond (Stochastic Environmental Research and Risk Assessment, 2007)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

Thermophilic bacterial DNA polymerases with reverse-transcriptase activity - Kate Griffiths; Harini Shandilya; Elizabeth K. Flynn; Mekbib Astatke; Po-Jen Shih; Jun E. Lee; Gary F. Gerard; Moreland D. Gibbs; Peter L. Bergquist (Extremophiles, 2004)

Longitudinal stratification of gait economy in young boys and girls: the locomotion energy and growth study - Jennifer L. Caputo; Daniel J. Keefer; Ian S. Craig; Kelly B. Griffith; Mary Beth Akins; Gareth E. Griffith; Gary S. Krahenbuhl; Philip E. Martin; Don W. Morgan; Wayland Tseh (European Journal of Applied Physiology, 2004)

Carbon isotope fractionation during dark respiration and photorespiration in C3 plants - Jaleh Ghashghaie; Franz-W. Badeck; Gary Lanigan; Salvador Nogués; Guillaume Tcherkez; Eliane Deléens; Gabriel Cornic; Howard Griffiths (Phytochemistry Reviews, 2003)

A technique for the molecular genetic analysis of Daphnia resting eggs from sub-recent lake sediments - Vicky A. Reid; Gary R. Carvalho; D. Glen George; Huw I. Griffiths (Journal of Paleolimnology, 2002)